Comparison of ProSeal Laryngeal Mask Airway & Supreme Laryngeal Mask Airway as Ventilatory Devices - Keshav Dev Jagar; Lokesh Kumar Gupta (Asian Journal of Medical Research, 2019)
Background: The present study was conducted to compare Proseal-Laryngeal Mask Airway and Supreme laryngeal mask airway (SLMA) in patients.Subjects and Methods:The present study was conducted on 40 patients of both genders. Patients were divided into 2 groups of 20 each. Group I patients were given supreme laryngeal mask airway and group II were given ProSeal laryngeal mask airway. All the devices were checked, prepared, inserted and secured.Results:The number of attempt in group I and II was 1, insertion time was 16.4 seconds in group I and 21.5 seconds in group II. Duration of anesthesia in group I was 61.8 minutes and in group II was 61.2 minutes, duration of pneumoperitoneum in group I was 62.4 minutes and 62. 8 minutes in group II. Insertion time NG tube in group I was 10.2 minutes and in group II was 8.4. The difference was significant (P< 0.05).in group I (cm H2O), OLP1 was 29.2 and in group II was 34.8, OLP2 in group I was 27.9 and in group II was 33.2, OLP3 in group I was 28.5 and in group II was 34.9. The difference was significant (P< 0.05).Conclusion: ProSeal laryngeal mask airway better as compared to supreme laryngeal mask airway.